Patents by main technology and by International Patent Classification (IPC) (Edition 2021) (OECD Patent Statistics, 2021)
This dataset comprises statistics on patents by main technology and International Patent Classification (IPC). EPO, USPTO, PCT and Triadic Patent Families are in fact presented according to classes of the International Patent Classification (IPC class up to 4 characters) and for selected technology domains such as ICT, nanotechnology, biotechnology as well as environment-related technologies. Data are presented from 1976 onwards